Efisiensi Saluran Irigasi di Daerah Irigasi Senden Kabupaten Sukoharjo - Aslam Taqiuddin; Agus Hari Wahyudi; Sobriyah Sobriyah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The irrigation efficiency is an important component on assessing the performance of an irrigation system. The analysis of irrigation loss is needed to obtain the amount of water lost along the channel. Water loss can be caused by a variety of factors, including water leakage along the canal, evaporation, and infiltration. This can certainly reduce the efficiency of water use. Irrigation a water loss analysis is very important to improve irrigation performance. This analysis will help you understand how much water is lost and what factors contribute to water loss. Based on this understanding, preventive measures can be taken and improvements can be made to increase productivity and water use efficiency. This research aims to evaluate the level of channel efficiency and measure the amount of water loss in the main channel in the Senden Irrigation Area.. The method of research implementation is to measure water discharge directly in the field. The result analysis showed that the average percentage of water loss in Senden main canal was 56.63%. Maximum water loss value was recorded at 60.86%, while the minimum value was 52.55%. Factors affecting water loss due to evaporation showed an average value of 0.0685%, while water loss due to seepage was recorded at a very small 0.0003%. For the channel efficiency value shows that an average percentage of 43%. It is obtained with a maximum channel efficiency of 47% and a minimum channel efficiency of 39%. However, the water balance analysis shows a maximum value of 11.45 m3 /second. While the minimum value is -0.04 m3 / second.